Completing the global inventory of plants – species discovery and diversity - Goodwin, ZA (2017)
To complete an online world Flora by 2020 rapid progress is required towards understanding the taxonomy and distributions of the world’s plants. This ambitious target set by the Global Strategy for Plant Conservation is hampered by two facts; first, many species of seed plant remain poorly known and second, the process of improving taxonomy and discovering species is not well understood. Here I investigate in detail the taxonomy and process of species discovery in a genus of tropical plants, Aframomum by examining specimens, taxonomic literature and authors of specimen determinations. I demonstrate that >50% of Aframomum specimens did not have the correct name prior to a recent comprehensive revision, that the number of specimens in herbaria doubled between 1970 and 2000, and that these results are also found in other taxa. I deconstruct the process of ‘species discovery’ by identifying four key events: Initial collection, publication, conservation assessment, and distribution mapping. The time lags between the initial collection and completion of a) an accurate conservation assessment (101 years) and b) a comprehensive distribution map (115 years) demonstrate that many seed plant species published in the last 100 years are not fully understood. This is partly due to the fact that most species protologues (>90%) cite too few specimens at publication to produce an accurate conservation assessment. Furthermore, I explore variation in species’ distribution patterns over time, taking account of specimen misidentification. Taken together the thesis identifies the lack of taxonomic capacity to efficiently deal with the tremendous influx of specimens since 1970, the poor current state of taxonomic knowledge of many taxa, and three significant time lags in the process of species discovery. Focused taxonomic effort is required for the successful completion of a world online Flora with conservation assessments to meet the 2020 GSPC target.